2018
DOI: 10.1016/j.livres.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in non-alcoholic fatty liver disease and alcoholic liver disease

Abstract: Autophagy is an evolutionarily conserved intracellular degradative function that is important for liver homeostasis. Accumulating evidence suggests that autophagy is deregulated during the progression and development of alcoholic and non-alcoholic liver diseases. Impaired autophagy prevents the clearance of excessive lipid droplets (LDs), damaged mitochondria, and toxic protein aggregates, which can be generated during the progression of various liver diseases, thus contributing to the development of steatosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 70 publications
0
63
0
Order By: Relevance
“…37 Autophagy has been implicated as a key regulatory factor in the pathogenesis of NAFLD. 21 Autophagy activation is considered one of the pathways in lipid clearance (lipophagy) and is associated with blocking of NASH. 38,39 The expression of LC3-II and the autophagic adaptors p62 are commonly used to monitor autophagy influx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Autophagy has been implicated as a key regulatory factor in the pathogenesis of NAFLD. 21 Autophagy activation is considered one of the pathways in lipid clearance (lipophagy) and is associated with blocking of NASH. 38,39 The expression of LC3-II and the autophagic adaptors p62 are commonly used to monitor autophagy influx.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that autophagy enhancement might be responsible for the protective role during NAFLD/NASH. 21 As a result, we measured autophagy in hepatic cells after Sal treatment. LC3B, an autophagy indicator, which correlates with the content of autophagosomes reflects the activity of autophagosomes.…”
Section: Sal Enhanced Autophagy In L02 Cells Treated With Pamentioning
confidence: 99%
“…[1][2][3] The overlap in the pathophysiology of NASH and muscle wasting make it challenging to determine whether muscle wasting is a risk factor for NASH or whether it is a complication of NASH. [4][5][6][7][8][9][10] Hepatic expression of SIRT1 is downregulated in NASH animals. 5 In transgenic mice, activation of SIRT1 protects against high-fat (HF)-induced hepatic oxidative stress and fatty liver.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that autophagy is harmed in patients with NAFLD [46,47]. Many factors involved in endoplasmic reticulum stress, insulin resistance, and mitochondrial dysfunction have been demonstrated to conduce to the exacerbation of NAFLD and are related to the disability of autophagy in the context of NAFLD [47].…”
Section: Discussionmentioning
confidence: 99%